Heart Rate Variability Parameter Changes in Patients With Acute Ischemic Stroke Undergoing Intravenous Thrombolysis - Yang Qu; Ying‐Ying Sun; Reziya Abuduxukuer; Xiang‐Kun Si; Peng Zhang; Jia‐Xin Ren; Yu‐Li Fu; Ke‐Jia Zhang; Jia Liu; Pan‐Deng Zhang; Hang Jin; Yi Yang; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Autonomic dysfunction has been revealed in patients with acute ischemic stroke and is associated with poor prognosis. However, autonomic nervous system function assessed by heart rate variability (HRV) and its relationship with clinical outcomes in patients undergoing intravenous thrombolysis (IVT) remain unknown. Methods and Results Patients who did and did not undergo IVT between September 2016 and August 2021 were prospectively and consecutively recruited. HRV values were measured at 1 to 3 and 7 to 10 days after stroke to assess autonomic nervous system function. A modified Rankin scale score ≥2 at 90 days was defined as an unfavorable outcome. Finally, the analysis included 466 patients; 224 underwent IVT (48.1%), and 242 did not (51.9%). Linear regression showed a positive correlation of IVT with parasympathetic activation‐related HRV parameters at 1 to 3 days (high frequency: β=0.213, P=0.002) and with both sympathetic (low frequency: β=0.152, P=0.015) and parasympathetic activation‐related HRV parameters (high frequency: β=0.153, P=0.036) at 7 to 10 days after stroke. Logistic regression showed HRV values and autonomic function within 1 to 3 and 7 to 10 days after stroke were independently associated with 3‐month unfavorable outcomes after adjusting for confounders in patients who underwent IVT (all P<0.05). Furthermore, addition of HRV parameters to conventional risk factors significantly improved risk‐predictive ability of 3‐month outcome (the area under the receiver operating characteristic curve significantly improved from 0.784 [0.723–0.846] to 0.855 [0.805–0.906], P=0.002). Conclusions IVT positively affected HRV and autonomic nervous system activity, and autonomic function assessed by HRV in acute stroke phase was independently associated with unfavorable outcomes in patients undergoing IVT.